2017
DOI: 10.1155/2017/1891849
|View full text |Cite
|
Sign up to set email alerts
|

Carlina vulgaris L. as a Source of Phytochemicals with Antioxidant Activity

Abstract: The methanol extracts from three populations of Carlina vulgaris L. were examined for the chlorogenic acid content, mineral content, total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity. Two populations originated from natural nonmetallicolous habitats (NN (populations from Nasiłów) and NP (populations from Pińczów)), and one metallicolous population (MB) was collected from Bolesław waste heap localized at the place of former open-cast mining of Ag-Pb and Zn-Pb ores dating back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 24 publications
1
25
1
Order By: Relevance
“…Xerothermic and calcareous grasslands are natural habitats of these plants [14]. However, Carlina genus plants are also found in HM-contaminated areas, for example, waste deposits from metal mining and smelting [15]. As a pseudometallophyte, C. acaulis can be an attractive object to study the HM tolerance and detoxification mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Xerothermic and calcareous grasslands are natural habitats of these plants [14]. However, Carlina genus plants are also found in HM-contaminated areas, for example, waste deposits from metal mining and smelting [15]. As a pseudometallophyte, C. acaulis can be an attractive object to study the HM tolerance and detoxification mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Despite naturally occurring antioxidant systems in the human body, reactive oxygen species cause lipid, protein, and DNA oxidation. These damages at the molecular level may influence the etiology of diseases, such as cancer, kidney failure, atherosclerosis, diabetes, hepatotoxicity, neurodegenerative disorders, and aging-related diseases 2 . It has been demonstrated that antioxidant substances may be defensive against above mentioned diseases.…”
mentioning
confidence: 99%
“…In an earlier work, Kováčik and Klejdus [9] observed significant elevation of chlorogenic acid in the related species chamomile (Asteraceae family) after prolonged exposure even to a low Cd concentration (3 µM), indicating that chlorogenic acid has probably more general antioxidative action. On the other hand, the negative effect of multi-heavy metal stress on chlorogenic acid accumulation has also been observed in Carlina vulgaris plants collected from metalliferous areas [15]. The authors found that plants inhabiting heavy metal polluted areas accumulated less soluble phenolics and flavonoids and exhibited lower antioxidant capacity than plants from non-polluted regions.…”
Section: Several Mechanisms Of CD Effect On the Uptake Of Essential Nmentioning
confidence: 97%
“…species that tolerate soils with high content of heavy metals. Two species, Carlina acaulis L. and Carlina vulgaris L., are part of the flora of calamine areas located in the metalliferous sites of Bolesław, in Southern Poland [14,15].…”
mentioning
confidence: 99%